(3w-24)(24w-3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

3w-24=0

24w-3=0

Set the first factor equal to 0.

3w-24=0

Add 24 to both sides of the equation.

3w=24

Divide each term by 3 and simplify.

Divide each term in 3w=24 by 3.

3w3=243

Cancel the common factor of 3.

Cancel the common factor.

3w3=243

Divide w by 1.

w=243

w=243

Divide 24 by 3.

w=8

w=8

w=8

Set the next factor equal to 0.

24w-3=0

Add 3 to both sides of the equation.

24w=3

Divide each term by 24 and simplify.

Divide each term in 24w=3 by 24.

24w24=324

Cancel the common factor of 24.

Cancel the common factor.

24w24=324

Divide w by 1.

w=324

w=324

Cancel the common factor of 3 and 24.

Factor 3 out of 3.

w=3(1)24

Cancel the common factors.

Factor 3 out of 24.

w=3⋅13⋅8

Cancel the common factor.

w=3⋅13⋅8

Rewrite the expression.

w=18

w=18

w=18

w=18

w=18

The final solution is all the values that make (3w-24)(24w-3)=0 true.

w=8,18

The result can be shown in multiple forms.

Exact Form:

w=8,18

Decimal Form:

w=8,0.125

Solve for w (3w-24)(24w-3)=0